Penyusunan Jobsheet Kendali Motor Servo Berbasis Human Machine Interface - Ikhwani Ikhwan; Muldi Yuhendri (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
One of the Practice courses for the D3 Electrical Engineering study program at the Electrical Engineering Department is Electrical Machine Control Practice. One of the materials given in this Electric Machine Control Practice is servo motor control. Along with technological developments, in the electrical energy conversion laboratory as a place for Electrical Machine Control Practice, a servo motor control training kit is available using a Programmable Logic Controller (PLC) and Human Machine Interface (HMI). Based on the observations made, the PLC and HMI-based servo motor control training kit does not yet have a manual or jobsheet as a guide for students and lecturers in carrying out practical activities. Therefore, in this study it is proposed to make a servo motor control jobsheet based on PLC and HMI using the Siemen S7 1200 PLC training kit with a Sinamic V90 servo motor driver and HMI TP 700 Comfort. The feasibility of the jobsheet is assessed from the validity, practicality and effectiveness tests with research procedures following the 4D development research method, which consists of the stages of define, design, development and dissemination stages. Based on the results of the tests carried out, the validity test results are obtained in the very valid category, the practicality test results are in the very practical category and the effectiveness test results are in the effective category. So that the jobsheet can be considered feasible to be used as a guide in implementing PLC and HMI-based servo motor control practices.